Proton storage in the periphery of zirconium(IV) porphyrinogen - Bachmann, Julien; Teets, Thomas S.; Nocera, Daniel G. (Dalton Transactions, 2008)
The reaction of zirconium(IV) porphyrinogen with water yields a dinuclear complex in which one mu-oxo ligand bridges two Zr-IV centres, and two protons are bound to the alpha carbons of two porphyrinogen pyrroles. The reaction establishes the utility of the porphyrinogen macrocycle as a storage site for protons as well as electrons.